2, 4‐D‐induced parthenocarpy in pear is mediated by enhancement of GA4 biosynthesis. Issue 3 (4th November 2018) - Cong, Liu; Yue, Rongrong; Wang, Huibin; Liu, Jianlong; Zhai, Rui; Yang, Jie; Wu, Meng; Si, Min; Zhang, Haiqi; Yang, Chengquan; Xu, Lingfei; Wang, Zhigang
Abstract : Parthenocarpy, the productions of seedless fruit without pollination or fertilization, is a potentially desirable trait in many commercially grown fruits, especially in pear, which is self‐incompatible. Phytohormones play important roles in fruit set, a process crucial for parthenocarpy. In this study, 2, 4‐dichlorophenoxyacetic acid (2, 4‐D), an artificially synthesized plant growth regulator with functions similar to auxin, was found to induce parthenocarpy in pear. Histological observations revealed that 2, 4‐D promoted cell division and expansion, which increased cortex thickness, but the effect was weakened by paclobutrazol (PAC), a gibberellin (GA) biosynthesis inhibitor. Phenotypic differences in pear may therefore be due to different GA contents. Hormone testing indicated that 2, 4‐D mainly induced the production of bioactive GA4, rather than GA3. Three key oxidase genes function in the GA biosynthetic pathway: GA20ox, GA3ox and GA2ox . In a pear group treated with only 2, 4‐D, PbGA20ox2‐like and PbGA3ox‐1 were significantly upregulated. When treated with 2, 4‐D supplemented with PAC, however, expression levels of these genes were significantly downregulated. Additionally, PbGA2ox1‐like and PbGA2ox2‐like expression levels were significantly downregulated in pear treated with either 2, 4‐D only or 2, 4‐D supplemented with PAC. We thus hypothesize that 2, 4‐D can induce parthenocarpy by enhancing GA4 biosynthesis.